Fear, dislike and hate : what constitutes xenophobia? : (an analysis of violence against foreigners in De Doorns, South Africa November, 2009) - Davis, Alexandra (Department of Social Development, 2014)
This paper provides an analysis of xenophobic violence in South Africa. By examining the root of the term 'xenophobia' it is possible to show how the term has evolved to mean something entirely different in the present day. De Doorns, a small farming town in the Western Cape of South Africa is used as a case study, showing how the xenophobic violence that occurred there in November 2009 arose and manifested. Through informal interviews, analyses of available local and regional statistical data a picture of the xenophobia in De Doorns emerges and is then examined in terms of the current theories on xenophobia. The resulting finding provide some new insight into xenophobia in South Africa and how it is evolving. Past assumptions that locate the root of xenophobic sentiment leading to xenophobic action in a 'hatred' of foreigners may be mistaken as xenophobia can (and does) occur in areas with low levels of prejudice towards foreigners. It does so because dissatisfaction with the government sometimes results in a new form of protest that is, to all appearances, xenophobia, but is not necessarily motivated by xenophobic intent. Rather an underlying xenophobic sentiment that exists throughout the nation has opened the door for poor South Africans to target foreign Africans a tool of protest in order to gain government attention. The whole concept of 'xenophobia' has evolved far beyond its roots to refer to actions that are taken against foreigners for the simple reason that they are foreign. As attacks on foreigners occur with increasing frequency in South Africa it is ever more important to gain a deep understanding of each individual outbreak in order to create a holistic and informed picture of South African xenophobia. This research suggests that some of the basic questions underlying research into xenophobia to be questioned.